An embedded randomised controlled trial of a Teaser Campaign to optimise recruitment in primary care - Lee, H; Hübscher, M; Moseley, G; Kamper, S; Traeger, A; Skinner, I; Williams, C; McAuley, J (SAGE Publications, 2017)
Background: Marketing communication and brand identity is a fundamental principle of advertising and end-user engagement. Health researchers have begun to apply this principle to trial recruitment in primary care. The aim of this study was to evaluate whether a Teaser Campaign using a series of postcards in advance of a conventional mail-out increases the number of primary care clinics that engage with a clinical trial. Methods: Embedded randomised recruitment trial across primary care clinics (general practitioners and physiotherapists) in the Sydney metropolitan area. Clinics in the Teaser Campaign group received a series of branded promotional postcards in advance of a standard letter inviting them to participate in a clinical trial. Clinics in the Standard Mail group did not receive the postcards. Results: From a total of 744 clinics that were sent an invitation letter, 46 clinics in the Teaser Campaign group and 40 clinics in the Standard Mail group responded (11.6% total response rate). There was no between-group difference in the odds of responding to the invitation letter (odds ratio = 1.18, 95% confidence interval = 0.75–1.85, p = 0.49). For physiotherapy clinics and general practice clinics, the odds ratios were 1.43 (confidence interval = 0.82–2.48, p = 0.21) and 0.77 (confidence interval = 0.34–1.75, p = 0.54), respectively. Conclusion: A Teaser Campaign using a series of branded promotional postcards did not improve clinic engagement for a randomised controlled trial in primary care.